Formulation and Evaluation of Nasal in situ Gel of Eletriptan Hydrobromide - Talele, Swati G. (Asian Journal of Pharmaceutics (AJP), 2024)
Aims: The nasal route has been found to be useful in targeting drugs to the central nervous system. As a target tissue for medication delivery, nasal mucosa has many advantages. Drug administration through the nose is related with systemic features a number of advantageous characteristics, including avoiding first-pass effects and having a sizable amount of surface area accessible for absorption. Materials and Methods: A new dosage form for nasal drug delivery, environment-sensitive gel has recently been used. In contrast to liquid nasal formulations, nasal in situ gels are injected into the nasal cavity as low-viscosity solutions. When the polymer comes into contact with the nasal mucosa, it changes conformation and forms a gel, which not only extends the time the drug is in contact with the absorptive sites in the nasal cavity but also allows the drug to be released gradually and continuously. Results and Discussion: This study set out to create and perfect a cold method-based nasal in situ gel formulation for Eletriptan Hydro bromide. Thermosensitive polymer was used to prepare nasal in situ gels. Study of Solgel transition temperature (Tsol-gel), rheological properties, in vitro release, and in vivo study was performed. Conclusion: Cumulative drug release from thesenasal in situ gel containing Eletriptan Hydro bromide was within the range of 42.92–86.12%. The cumulative drug release using nasal mucosa of goat was 70.44%. Th e enhanced nasal residence time, improved bioavailability, increased brain uptake of parent drug and decreased exposure of metabolites suggested that the in situ gel could be an effective intranasal formulation of Eletriptan Hydro bromide.